Pengaruh Profitabilitas, Likuiditas, Solvabilitas terhadap Nilai Perusahaan Industri Jasa: - Putri, Aqilla Tauhidta Arla; Wiyono, Gendro; Rinofah, Risal (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The Effect of Profitability, Liquidity, Solvability, on the Value of Service Industry Companies (Case Study of Building Construction Companies 2017-2021) listed on the Indonesia Stock Exchange. Aims to answer the problem of the influence of Profitability, Liquidity, Solvency on Firm Value in Building Construction Companies. In this study the method used is a quantitative approach. The population in this study were 18 building construction companies. Sampling was carried out using the non-probability method and the sampling technique was Purposive Sampling. Data analysis using the IBM SPSS application. The results of this study indicate that the variable Profitability (X1) has a significant effect on Firm Value (Y), as evidenced by the results of the t test, which is obtained from the t value 3.481 > t table 1.729 and a significance of 0.001 <0.05. Then the variable Liquidity (X2) has a significant effect on Firm Value (Y), as evidenced by the results of the t test, namely the t count value of 3.150 > t table 1.729 and a significance of 0.003 <0.05. And the Solvency variable (X3) has no effect on Firm Value (Y), as evidenced by the results of the t test, namely the t count value is 1.620 < t table 1.729 and the significance is 0.114 > 0.05. From the results of the F test it is proven that Profitability (X1), Liquidity (X2), and Solvability (X3) simultaneously influence Firm Value (Y). Keywords Profitability; Liquidity; Solvency; Firm Value